Intrapericardial Teratoma and Associated 3q29 Deletion in a Fetus: Case Report - Guralp, Onur; Schoner, Katharina; Wolter, Aline; Schenk, Johanna; Reitz, Maleen; Widriani, Ellydda; Froebius, Katrin; Weber, Axel; Axt-Fliedner, Roland (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Depending on its location, size, and proximity to the cardiac structures, an intrapericardial teratoma may lead to severe circulatory disturbances and even fetal demise. A 34-year-old G2P1 presented at 20w5d with a solid cystic mass in the right thorax of the fetus, originating from the right atrium or lung, with signs of non-immune fetal hydrops, soon resulting in intrauterine fetal death. Detailed post-mortem autopsy revealed signs of hydrops fetalis universalis due to a spherical tumor mass originating from the aortic root. Histologic examination of the tumor showed the characteristic morphology of a teratoma. A 1.6-Mb microdeletion at 3q29 was identified by single nucleotide polymorphism array. This is the first report presenting the diagnosis of an intrapericardial teratoma in a fetus with a microdeletion of 3q29. Intrapericardial teratoma has a poor prognosis and the fetal outcome relies on the development of hydrops. A post-mortem examination is essential in order to make a definitive diagnosis, which underlines the status of the fetal pathologist and the need for interdisciplinary cooperation.
Keywords: intrapericardial teratoma; fetal mediastinal teratoma; 3q29 microdeletion; fetal pathology